Thymus zygis Essential Oil: Phytochemical Characterization, Bioactivity Evaluation and Synergistic Effect with Antibiotics against Staphylococcus aureus - Alexandra Coimbra; Sónia Miguel; Maximiano Ribeiro; Paula Coutinho; Lúcia Silva; Ana Paula Duarte; Susana Ferreira (MDPI AG, 2022)
Staphylococcus aureus is a nosocomial bacterium causing different infectious diseases, ranging from skin and soft-tissue infections to more serious and life-threatening infections such as sepsis, meningitis and endocarditis, which may be exacerbated by antibiotic resistance. Plant products may be seen as an alternative as antibacterial agents, namely, against S. aureus. Thus, the aim of this work was to characterize the chemical composition and evaluate the bioactive properties of the T. zygis essential oil (EO), with a focus on antimicrobial activity against S. aureus. Gas chromatography coupled with mass spectrometry was used to assess the chemical composition of the T. zygis EO, and the antioxidant activity was evaluated using the DPPH method and β-carotene-bleaching assay. The antimicrobial activity against S. aureus strains, the interaction with different antibiotics and the attenuation of this bacterium's virulence were evaluated. The T. zygis EO showed antioxidant activity acting through two different mechanisms and antibacterial activity against S. aureus, with antibiofilm and antihaemolytic properties. This EO also demonstrated synergistic or additive interactions in combination with ampicillin, ciprofloxacin or vancomycin against S. aureus strains and, in some cases, changed the antibiotic-resistance phenotype from resistant to susceptible. Therefore, the present work demonstrates the good bioactive properties of the EO of T. zygis, mainly the antimicrobial activity against S. aureus, revealing its potential to be used as an antibacterial agent.